1, 2‐Epoxy Propane Induced Self‐Assembly of Macroscopic Graphene with Good Adsorption. Issue 13 (10th May 2017) - Gao, Bingying; He, He; Lu, Shaoxiang; Kalulu, Mulenga; Oderinde, Olayinka; Ren, Lili
Abstract: A universal and simple one‐step approach to fabricate three‐dimensional (3D) graphene materials with the aid of 1, 2‐epoxy propane (PO) has been reported in this paper. PO, as one of widely used engineering materials, is easy to produce ring‐opening reaction under acidic conditions. When PO is introduced into graphene oxide (GO) dispersion (pH=2.4‐3.8), a 3D graphene architecture will be formed through the reaction of PO with oxygen‐containing functional groups (i. e. epoxy, carbonyl and carboxyl groups) on the surface of GO sheets. The obtained 3D graphene monolithic exhibits high porosity, strong mechanical performance, and good adsorption capacities for oil and organic dyes, which may find potential applications in wastewater treatment, environmental remediation, and electrochemistry. Abstract : Three‐ dimensional (3D) graphene materials (PO‐GH and PO‐GA) were synthesized by one‐pot method with the aid of 1, 2‐epoxy propane (PO). The PO‐GA with a volume of 3.59 cm 3 can easily be supported by a leaf or petal. Moreover, the as‐prepared PO‐GH exhibits good adsorption capacities for organic dyes in water without losing their structural integrity.